Correction of Postural Disorders of Mature Age Women in the Process of Aqua Fitness Taking Into Account the Body Type - Nataliia Goncharova; Vitalii Kashuba; Anna Tkachova; Tamara Khabinets; Olha Kostiuchenko; Mariia Pymonenko (OVS LLC, 2020)
The purpose of the article is to develop and test the effectiveness of aqua fitness exercise program for the posture improvement of women of the first period of a mature age with different body types.  Materials and methods. The pedagogical experiment involved 46 women of the first period of a mature age who had previously consented to participate in the study. The used methods include the analysis and generalization of scientific and methodological literature, Internet data, and mathematical statistics methods, including Fisher's angular criterion, which allows sampling by distribution of the trait (Byshevets et al., 2019). The research included the assessment of the posture condition of women based on the method of visual screening of posture with determination of the total score (Kashuba et al., 2016). A surgeon was also involved in assessing the posture of women. In the process of factor analysis, the data of anthropometric studies, physical fitness assessments, and motor activity level were analyzed.  Results. The distribution of women of the first period of a mature age by types of postural disorders and its changes under the influence of aqua fitness classes taking into account the body type has been established. The study involved 46 women of the mentioned category; 73.9% of them were women of normosthenic body type, 15.2% - of asthenic type, and 10.9% - of hypersthenic type. The research has established that women who were engaged in aqua fitness with regard to body type had positive changes in posture. The proportion of women of asthenic body type with a normal posture increased by 28.6%, of normosthenic type - by 20.6%, and of hypersthenic type - by 20.0%. Changes occurred in the level of the bio-geometric profile of the posture.  Conclusions. The study confirms the effectiveness of the use of aqua fitness in the process of health-promoting classes to prevent and correct postural disorders.